Studies on the Effect of Starvation on Prolonged Callus Cultures and Alterations in SERK Gene Expression during Somatic Embryogenesis in Momordica charantia Linn. (Plant Tissue Culture and Biotechnology, 2021)
Abstract not availablePlant Tissue Cult. & Biotech. 31(1): 109-114, 2021 (June)